Anatomy and evolution in Cylindrostomidae (Plathelminthes, Prolecithophora). - Karling, T. G. (Zoologica Scripta, 1993)
The following species of Cylindrostomidae are redescribed: Cylindrostoma lutheri Westblad, 1955, C. micropharynx Westblad, 1952, Monoophorum tubiferum Westblad, 1955, M. stiliferum Westblad, 1955 (transferred to Einarhelmins gen. n.), Allostoma crassicystiferum (Westblad, 1952), A. uterinum (Westblad, 1955), and Euxinia baltica Meixner, 1938. Three new species are described: Cylindrostoma paralutheri, Allostoma neostiliferum and A. hopkinsi. A review is given on anatomy and evolutionary trends in Cylindrostomidae